Teaching Philosophy by the Use of Thought Experiments: The Quantum Approach to the Problem of Qualia - Bregant, Janez; Aberšek, Boris (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
One of the hard questions in the philosophy of mind is how to place something like consciousness, which we find unique, into the physical world in a way that it does not lose its originality. The biggest obstacle to overcome seems to be the absence of a clear mechanism that would thoroughly explain how phenomenal states emerge from the brain. The trouble is that experience is always subjective and, as such, cannot be captured by objective scientific explanations. This paper shows how by the use of thought experiments in teaching philosophy, in our case the »Chinese room«, this problem could be addressed, and tries to find out if perhaps the indeterministic quantum mechanics can answer the question of how consciousness arises in our brain. It argues for the claim that the quantum approach to consciousness leads to the idealistic ontology rather than to the physical explanation of how it comes into being.